Csaba G. Kiss, Lekcja Europy Środkowej. Eseje i szkice. Kraków 2009, ss. 318 - Piotrowiak-Junkiert, Kinga (Porównania, 2012)
Csaba G. Kiss, Lekcja Europy Środkowej. Eseje i szkice. Kraków 2009, ss. 318